SUDDEN UNEXPECTED DEATHS DUE TO TUBERCULOSIS: AN AUTOPSY BASED STUDY (Journal of Forensic Medicine & Toxicology, 2012)
Purpose: Mycobacterium tuberculosis is estimated to infect 1.6 billion people worldwide and killing around 2- 3 million people annually. This autopsy based retrospective research was conducted to understand the pattern of sudden deaths from tuberculosis in Mangalore, South India. Methods: The study was conducted at the Department of Forensic Medicine, Kasturba Medical College, Mangalore and autopsy case files during May 2004 to April 2008 were studied. Histopathologically confirmed cases of sudden death due to tuberculosis were included in the study. Results: During the study period a total of seventy three cases of sudden deaths due to respiratory system involvement were reported. Of all sudden respiratory deaths, forty five cases (61.64%) were specifically assigned to tuberculosis. Males were predominantly affected (86.67%). Majority of deaths were reported in the 5th decade of life (33.33%). Most of the victims (84.44%) were underweight and emaciated. Findings were restricted to lungs in 82.22% cases while miliary spread was observed in 17.78 % cases. Conclusion: Active TB has implications for the health of autopsy room staff, autopsy room design and ventilation, choice of protective equipment and for the public health service. Steady increase in fatal cases of tuberculosis even with better treatment and diagnostic facilities is a cause of concern.
Keywords: Tuberculosis; Miliary tuberculosis; Sudden death; Autopsy; South India